Água, organização do território e desertificação na Tunísia: observações a partir de um trabalho de campo - Bartolomeu Israel de Souza; Rosa Maria Vieira Medeiros (Confins)
Desertification is a type of environmental degradation likely to occur in dry climate regions of the world, mainly because of the way the exploration of land located there happens. A great part of Tunisia is susceptible to this environmental impact, taking into account that considerable extensions of its territory have a predominance of very low rainfall. Nevertheless, the desertification will not always be present in those lands, whose presence is determined by the type and intensity of soils use. The field work developed in the central south region of this country where there are semi-arid and arid climates helped us observe different results related to this environmental issue. In one part of this region, management techniques of soil and water used in territorial organization, which were practiced for thousands of years, continue to be viable alternatives to the sustainability of agriculture and, along with the use of modern techniques, have prevented the depletion of soil and water resources. These examples show that the living with drought, coupled with economic production in a sustainable manner, is likely to occur in these environments. Some of these techniques can be performed in Brazil, particularly in the semi-arid northeastern region. Likewise, the control of movement of continental dunes was another positive aspect observed and it can also be reproduced in some areas of Brazil where this phenomenon occurs. On the other hand, it was realized that the increasing need for fertile land and water for use in commercial agriculture in Tunisia has been expanding this activity toward some parts of this region, which is still little explored for this purpose and present these natural resources. So that, it brings as a consequence the decline of the traditional use of these lands, originally based on extensive cattle raising, an activity that starts to be more intensely developed in places where water and vegetation are less abundant, causing a faster exploration of them. Thus, a super pasture is being developed and desertification is becoming a mark that is increasingly present in some landscapes of this part of the country.